Aspek-Aspek Tauhid dalam Islam, Rububiyah, Uluhiyah, Asma’u Wa Sifat - Harahap, Azrai; Dewi, Azzahra Kusuma (Jurnal Penelitian Multidisiplin Ilmu, 2025)
This paper aims to find out how the aspects of monotheism, namely monotheism rububiyah, uluhiyah, asma wasifat in life. Using library methods, collecting and analyzing data from all sources of information related to monotheism. The results obtained show that the explanation of monotheism is divided into three aspects, namely monotheism rububiyah, uluhiyah, asma wasifat, each of which has an important role in forming true faith. So that a deep understanding of these three aspects of monotheism can foster strong and solid beliefs, strengthen faith and prevent deviations in beliefs in religious life.